2007
DOI: 10.1074/jbc.m700765200
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic Lateral Sclerosis-associated Copper/Zinc Superoxide Dismutase Mutations Preferentially Reduce the Repulsive Charge of the Proteins

Abstract: We provide bioinformatical evidence that protein charge plays a key role in the disease mechanism of amyotrophic lateral sclerosis (ALS). Analysis of 100 ALS-associated mutations in copper/zinc superoxide dismutase (SOD1) shows that these are site-selective with a preference to decrease the proteins' net repulsive charge. For each SOD1 monomer this charge is normally ؊6. Because biomolecules as a rule maintain net negative charge to assure solubility in the cellular interior, the result lends support to the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
76
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 49 publications
(26 reference statements)
6
76
1
Order By: Relevance
“…Correlations between the properties of mutant SOD1 and ALS disease characteristics have been sought for many years and are critical for deciphering disease mechanisms. Previous studies have reported evidence for a weak inverse correlation between oxidized apo SOD1 stability and ALS disease duration (45)(46)(47), which improves when global or local protein characteristics such as charge (48) or hydrogen bonding (45) are considered. The results for V148I suggest that increased hydrophobicity of the exposed dimer interface may be another significant modulator of aggregation.…”
Section: Als-associated Mutations Have Complex Effects On Stability Andmentioning
confidence: 99%
“…Correlations between the properties of mutant SOD1 and ALS disease characteristics have been sought for many years and are critical for deciphering disease mechanisms. Previous studies have reported evidence for a weak inverse correlation between oxidized apo SOD1 stability and ALS disease duration (45)(46)(47), which improves when global or local protein characteristics such as charge (48) or hydrogen bonding (45) are considered. The results for V148I suggest that increased hydrophobicity of the exposed dimer interface may be another significant modulator of aggregation.…”
Section: Als-associated Mutations Have Complex Effects On Stability Andmentioning
confidence: 99%
“…Our data reveal molecular properties of SOD1 that may offer insight into the variations in disease propensity and progression observed among different mutants. Previous reports have shown that the net electric charge of SOD1 mutants is an important factor in ALS (14,28). Because the population of monomeric apo-SOD1 depends on a number of factors, including dimer interface integrity, metal affinity, and disulfide oxidation state, mutations compromising any of these properties would be expected to influence disease propensity (2, 11).…”
Section: Biophysics and Computational Biologymentioning
confidence: 99%
“…The monomeric apo states of A4V, G85R, and G93A are all highly destabilized toward global unfolding, whereas D90A imparts only a marginal effect in this respect (14). G85R and D90A have a lower net negative charge, which increases the aggregation propensity (14,28), and G85R has a lower metal affinity, which increases the relative population of apo-SOD1 (2). A4V and G93A confer short survival times in patients with ALS (Ͻ 3 years), while G85R and D90A are associated with more variable disease progression (1,2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These 4 dogs may have been misdiagnosed. The SOD1:c.118GϾA transition predicts an E40K missense with anionic membrane surfaces (10,25). A glutamate at a position corresponding to amino acid position 40 in canine SOD1 is conserved in 19 of 20 mammals identified in a Blastp query of the nonredundant protein sequences in the National Center for Biotechnology Information database (Fig.…”
Section: Dogs With Advanced Dm Have Both Upper and Lower Motor Neuronmentioning
confidence: 99%